Meristematic cell proliferation and ribosome biogenesis are decoupled in diamagnetically levitated Arabidopsis seedlings - Manzano, Ana Isabel; Larkin, Oliver J.; Dijkstra, Camelia E.; Anthony, Paul; Davey, Michael R.; Eaves, Laurence; Hill, Richard J.A.; Herranz, Raul; Medina, F. Javier (BioMed Central, 2013)
Background: Cell growth and cell proliferation are intimately linked in the presence of Earth’s gravity, but are decoupled under the microgravity conditions present in orbiting spacecraft. New technologies to simulate microgravity conditions for long-duration experiments, with stable environmental conditions, in Earth-based laboratories are required to further our understanding of the effect of extraterrestrial conditions on the growth, development and health of living matter. Results: We studied the response of transgenic seedlings of Arabidopsis thaliana, containing either the CycB1-GUS proliferation marker or the DR5-GUS auxin-mediated growth marker, to diamagnetic levitation in the bore of a superconducting solenoid magnet. As a control, a second set of seedlings were exposed to a strong magnetic field, but not to levitation forces. A third set was exposed to a strong field and simulated hypergravity (2 g). Cell proliferation and cell growth cytological parameters were measured for each set of seedlings. Nucleolin immunodetection was used as a marker of cell growth. Collectively, the data indicate that these two fundamental cellular processes are decoupled in root meristems, as in microgravity: cell proliferation was enhanced whereas cell growth markers were depleted. These results also demonstrated delocalisation of auxin signalling in the root tip despite the fact that levitation of the seedling as a whole does not prevent the sedimentation of statoliths in the root cells. Conclusions:In our model system, we found that diamagnetic levitation led to changes that are very similar to those caused by real- [e.g. on board the International Space Station (ISS)] or mechanically-simulated microgravity [e.g. using a Random Positioning Machine (RPM)]. These changes decoupled meristematic cell proliferation from ribosome biogenesis, and altered auxin polar transport.